2021
DOI: 10.15403/jgld-3687
|View full text |Cite
|
Sign up to set email alerts
|

Negative Effects of Endoscopists’ Fatigue on Colonoscopy Quality on 34,022 Screening Colonoscopies

Abstract: Background and Aims: There is still considerable controversy surrounding the relationship between fatigue of endoscopists and the quality of colonoscopy. The aim of this study is to comprehensively explore the association between fatigue and adenoma detection rate (ADR) and cecal intubation rate (CIR). Methods: The mixed effects logistic regression model was used to explore the relationship between fatigue- related factors including procedure order, session of procedures and the day of week and ADR as we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
5
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 19 publications
1
5
0
Order By: Relevance
“…Regarding procedure day, several quality markers (including withdrawal time for negative procedures, and use of hyoscine butylbromide) -were worse for weekend than weekday procedures. Moreover, mean number of points per list was also higher at weekends, consistent with other studies which indicate that greater (cumulative) workload may be associated with endoscopist fatigue, or pressure to save time by cutting corners, and hence lead to lower detection [28][29][30]. Many of these markers have been associated with ADR in UK endoscopy practice [31] and, unlike case-mix, they are, at least to some extent, under the control of the endoscopist or unit and, hence, potentially modifiable.…”
Section: Discussionsupporting
confidence: 89%
“…Regarding procedure day, several quality markers (including withdrawal time for negative procedures, and use of hyoscine butylbromide) -were worse for weekend than weekday procedures. Moreover, mean number of points per list was also higher at weekends, consistent with other studies which indicate that greater (cumulative) workload may be associated with endoscopist fatigue, or pressure to save time by cutting corners, and hence lead to lower detection [28][29][30]. Many of these markers have been associated with ADR in UK endoscopy practice [31] and, unlike case-mix, they are, at least to some extent, under the control of the endoscopist or unit and, hence, potentially modifiable.…”
Section: Discussionsupporting
confidence: 89%
“…Furthermore, it may disrupt the schedule of the endoscopist, resulting in a possible hastened withdrawal with a higher chance of overlooking polyps. [17][18][19][20] On the contrary, some previous studies have shown no direct relationship between cecal intubation time and the number of detected adenomas. 8,9 Instead, they have suggested that the cecal intubation time to withdrawal time ratio (IWTR) was a quality indicator of adenoma detection, as IWTR <1.0 was associated with the detection of more adenomas compared with IWTR ≥1.0.…”
Section: Discussionmentioning
confidence: 84%
“…Furthermore, it may disrupt the schedule of the endoscopist, resulting in a possible hastened withdrawal with a higher chance of overlooking polyps. 17 , 18 , 19 , 20 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although other factors such as selection time and time taken to advance the images were not considered, it is unlikely that a human would be able to outperform AI in terms of speed. Furthermore, unlike the human endoscopist, 20 the AI system is not fatigable, the accuracy of AI would remain the same when evaluating the first picture to the 300th picture, however this may not be true for the endoscopist. The comparison between the AI and the endoscopist is summarized in figure 1.…”
Section: Discussionmentioning
confidence: 99%